Introducing VAR and SVAR predictions in system dynamics models. (6th October 2008) - Alvarez-De-Toledo, Pablo; Crespo Marquez, Adolfo; Nunez, Fernando; Usabiaga, Carlos
Vector Autoregressive (VAR) and Structural Vector Autoregressive (SVAR) models may be described as those models that explain, at least partially, the values of a set of variables, based on the past values of this set of variables. During recent decades, these models have increased their importance in the field of economic analysis. In this work, we offer an approximation between these econometric techniques and the methodology of system dynamics. We show that by using usual elements in the models of system dynamics we can carry out the simulation of an SVAR model. We present an application to the Spanish labour market.